Motion error and accuracy evaluation method for CNC vertical milling machine - Mohd Shukor, Mohd Khairul Rizal (2014)
This report represents a method that uses the double ball bar to inspect motion errors of the rotary axes of three axis CNC milling machine tools. This method uses a particular circular test path that only causes the two rotary axes to move simultaneously and keeps the other linear axes stationary. Therefore, only motion errors of the two rotary axes will be measured during the double ball bar test. Minimum circular radius that can be inspecting with standard double ball bar circular interpolation test kit is l 50mm. Therefore, machine with less than 150mm circular radius need to use measuring magnification in order to enable the circular interpolation test by double ball bar method. The characteristic of measuring magnification for machine with circular radius less than 150mm is proposed. The theoretical trace pattern of error origins which is squareness error is established. Consequently, the error origins in the rotary block can be diagnosed by examining whether similar patterns appear in the motion error trace. Testing procedure performed by means of detecting the motion errors characteristic. Then based from this trace pattern, the current state of the machines can be known and this information is beneficial for the user to take necessary actions.